Edukasi Gizi terhadap Sikap Gemar Makan Sayur Kepada Anak Usia Sekolah - Retno Ayu Hapsari; Agnescia Clarissa Sera; Oriza Aditya (Jurnal Forum Kesehatan : Media Publikasi Kesehatan Ilmiah, 2022)
Abstract – Vegetables contain vitamins, minerals, and dietary fiber. The body uses a number of vitamins and minerals from fruits and vegetables as antioxidants or as a defense against dangerous substances. By consuming enough veggies, the risk of developing unhealthy cholesterol, blood sugar, and blood pressure can be reduced. In Indonesia, fruit and vegetable consumption is still on the low side. This study sought to examine how children of school age perceived the benefits of consuming vegetables. Pre-experimental research is being done. Using the "purposive sampling" method, a sample of 26 grade VI SDN students in city X were chosen by answering 20 statement items both before and after taking part in counseling or nutrition instruction regarding serving vegetables to school-age children. One group pretest-posttest was the chosen research design. The "Paired Samples t Test" technique was used to examine the data, and the results were used to quantify the change (gain) in the students' attitude ratings toward the practice of eating vegetables. The findings demonstrated that children of school age had a different attitude about eating vegetables as a result of nutrition instruction. Because knowledge has an impact on attitudes, behaviors, and habits, it is crucial to provide nutrition education. The results of this study should serve as a guide for parents, educators, and the general public as they continue to stress the value of consuming vegetables, particularly for young children attending school.